Sport Specialization and Single-Legged–Squat Performance Among Youth Baseball and Softball Athletes - Barfield, Jeff W. (J Athl Train, 2019)
CONTEXT: Previous research has indicated that throwing sports expose athletes to overuse injuries and that specialization in sport is linked to injury. However, the effect of overexposure to a throwing sport on a dynamic movement task is unknown. OBJECTIVE: To determine if sport specialization in youth throwing athletes affected performance on the single-legged squat (SLS). DESIGN: Descriptive laboratory study. SETTING: University research laboratory. PATIENTS OR OTHER PARTICIPANTS: A total of 49 youth baseball and softball athletes (23 baseball, 26 softball; age = 12.96 ± 2.32 years, height = 165.01 ± 13.05 cm, mass = 61.42 ± 13.04 kg) were recruited. MAIN OUTCOME MEASURE(S): Participants were grouped into 3 categories based on specialization definitions: (1) 8 months or longer in season, (2) 8 months or longer in training, or (3) 8 months or longer in season and previously quit another sport. We measured SLS kinematics and used a set of 1-way multivariate analyses of variances to determine if trunk kinematics differed by group. RESULTS: Athletes who spent 8 months or more in sport-specific training exhibited significantly more trunk control, revealed by less trunk lateral flexion (Λ = 0.69, F(6,38) = 2.89, P = .020) and less trunk flexion (Λ = 0.69, F(6,38) = 2.88, P = .021) throughout an SLS. CONCLUSIONS: These results agree with the principle of specific adaptation to imposed demands. Surprisingly, athletes who spent 8 months or more playing a unilateral sport showed no differences in SLS performance. Clinicians should emphasize that neuromuscular adaptations of the lumbopelvic-hip complex for dynamic movement, such as an SLS, may be achieved through training instead of strict sport participation. Future researchers should consider how much of the training protocol is actually specialized for sport training.